First field trial of optical label-based switching and packet drop on a 477 km NTON/Sprint link - Hernandez, V.J.; Pan, Z.; Cao, J.; Tsui, V.K.; Bansal, Y.; Fong, S.K.H.; Zhang, Y.; Jeon, M.Y.; Yoo, S.J.B.; Bodtker, B.; Bond, S.; Lennon, W.J.; et al. (Optical Fiber Communications Conference: Post Conference Digest, 2002)
We have demonstrated for the first time in our knowledge optical label-based wavelength switching and packet drop over actual field fiber. We have shown SCM-formatted optical labeling transmission with less than 2 dB power penalty for both label and payload over 476 km of fiber. The optical label switching achieves packet drop and re-transmission of the remaining packet.